2011
DOI: 10.1016/j.carj.2010.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of Incidental Findings in a Lung Cancer Screening Study by Using Low-dose Computed Tomography

Abstract: IFs on lung cancer screening studies are not uncommon and frequently require imaging or other follow-up for definitive diagnoses and to assess their clinical relevance. The implication of IFs has to be considered when determining a cost-effective and ethical protocol for the utilisation of LDCT in a high-risk population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(71 citation statements)
references
References 29 publications
2
65
1
2
Order By: Relevance
“…This proportion is consistent with our results. In addition, technological advancements in imaging modalities and various screening programs have increased the prevalence of incidental findings of malignancies, which in turn increases the number of referrals of patients for palliative radiation [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…This proportion is consistent with our results. In addition, technological advancements in imaging modalities and various screening programs have increased the prevalence of incidental findings of malignancies, which in turn increases the number of referrals of patients for palliative radiation [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…We note that only the effect of including costs and consequences of incidental findings would be indeterminate. Although it is probable that incidental findings would generate additional work-up and imaging costs (studies in both Canada 108 and Italy 109 have reported costs equivalent to around Β£9 per participant), it is equally likely that the earlier diagnosis of these non-cancer conditions could potentially generate compensating outcome gains.…”
Section: Uk Lung Cancer Screening Evaluation Modelmentioning
confidence: 99%
“…There is no reliable information on the costs of managing potentially significant incidental findings; however, 2 recent studies of lung cancer screening with CT in Italy and Canada reported radiologic costs of $129 21 and $95 22 per finding. In a study of incidental findings in CT colonography in the United States, total medical costs were about $1600 per finding, only about one third of which was due to radiologic imaging.…”
Section: Methodsmentioning
confidence: 99%